2008
DOI: 10.1177/0022219408321123
|View full text |Cite
|
Sign up to set email alerts
|

Are Reading and Behavior Problems Risk Factors for Each Other?

Abstract: We investigated two questions. First, are children with reading problems in first grade more likely to experience behavior problems in third grade? Second, are children with behavior problems in first grade more likely to experience reading problems in third grade? We explored both questions by using multi-level logistic regression modeling to analyze data from the Early Childhood Longitudinal Study—Kindergarten Class (ECLS-K). After statistically controlling for a wide-range of potential confounds, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
193
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(229 citation statements)
references
References 100 publications
18
193
2
1
Order By: Relevance
“…Two more recent US studies have emphasized the phenomena of co‐occurrence. Morgan, Farkas, Tufis, and Sperling (2008) found that US children with reading problems at age 7 years were more likely to display poor task engagement, poor self‐control, externalizing and internalizing behaviour problems 2 years later. More recently, Dahle and colleagues (2010) examined behavioural problems in children with severe dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Two more recent US studies have emphasized the phenomena of co‐occurrence. Morgan, Farkas, Tufis, and Sperling (2008) found that US children with reading problems at age 7 years were more likely to display poor task engagement, poor self‐control, externalizing and internalizing behaviour problems 2 years later. More recently, Dahle and colleagues (2010) examined behavioural problems in children with severe dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Prior investigations have found a relation between internalizing behavior problems and reading achievement (Ackerman et al, 2007;Morgan et al, 2008). It may be the case that the heterogeneity of individuals with internalizing behavior problems contributed to the weak relation between internalizing and reading in the current investigation.…”
Section: Behavioral Engagementmentioning
confidence: 56%
“…Individuals with reading deficits have been found to exhibit more internalizing (Ackerman, Izard, Kobak, Brown, & Smith, 2007;Morgan, Farkas, Tufis, & Sperling, 2008;Undheim, Wichstrøm, & Sund, 2011;Willcutt & Pennington, 2000) and externalizing behavior problems (Undheim et al, 2011;Willcutt & Pennington, 2000) than children with typical reading achievement. Assessment of the contribution of internalizing and externalizing behavior problems to reading achievement could have implications for classroom instruction and identification of children who may be at risk for difficulty with reading.…”
Section: Relatedness and Reading Achievementmentioning
confidence: 99%
“…School-related problem behaviours such as inattentiveness or hyperactivity have been found to influence school readiness (eg, Tomblin et al, 2000;Hinshaw, 1992) and literacy (Morgan et al, 2008;Miles and Stipek, 2006). Miles and Stipek investigated longitudinal associations between social behaviour and literacy in young children at school entry.…”
Section: Introductionmentioning
confidence: 99%
“…The first is based on the notion that language or literacy difficulties (due to factors such as phonological difficulties or poverty) might trigger frustration, avoidance and withdrawal from language and literacy tasks (eg, Morgan et al, 2008;Miles and Stipek, 2006).This process may take time in that considering the emerging normative comparisons, as children grow older they become increasingly more aware of their abilities and performances in comparison to their peers, possibly, experiencing negative emotions that may set the stage for increased difficulties with social behaviour. The second explanation refers to behavioural difficulties (eg, hyperactivity, inattention) contributing to language, reading and writing difficulties.…”
Section: Introductionmentioning
confidence: 99%